Species composition and distribution of shrubs and herbs in a one hectare secondary forest along the cost of University of the Philippines in the Visayas campus, Brgy. mambatad, Miagao, Iloilo. - Mestidio, Sheila P
A one hectare plot in a secondary forest along the coast of UPV campus, Miagao, Iloilo was chosen as the study area. The scientific names of the shrubs and herb species were identified. The distribution of each shrub and herb species in reference to the area was noted. The physico-chemical were also taken., Nine hundred eighty six shrubs and herbs were found in the one-hectare plot. Thirty species were identified and ten species remained unkown. The top five most abundant species in the area were "gulipas" (Sida cordifolia), "hagonoy" (Chromolaena odorata), "bahu-baho" (Lantara camara), "katanda" (Cassia tora) and 'bagasua" (Ipomoea pes-caprae). Most species are found in clusters in an area and not uniformly distributed all throughout the study area. The soil temperature and pH values taken were all within the suitable soil fertility and plant growth conditions. The soil in the study area is largely comprised of sand component but generally favourable to plant growth.